Enhancing Effect of Silver Nitrate Nanoparticles as an Adjuvant in Formulation of Polyvalent Foot and Mouth Disease Vaccine (Global Journal of Medical Research, 2020)
Vaccination of susceptible animals against foot-and-mouth disease (FMD) is a wellestablished strategy to combat the disease. The protective immune response induced by vaccines can vary according to the kinds of adjuvants. The advance in nanotechnology has enabled us to utilize particles in the Nano size. So using novel immune adjuvants has an auxiliary role in the amplification of immune responses. Many investigators agree the size of the adjuvant particles is crucial to their adjuvant activities. The main aim of this study is to evaluate the effect of Silver nitrate nanoparticles (AgNPs) 5-10 nm particle size as an adjuvant in the polyvalent foot and mouth disease vaccine (containing FMD viruses O / PanAsia2, A/Iran 05, SAT2/VII/Lib-12 (SAT2/ Lib) and SAT2/VII/Ghb-12(SAT2/Ghb). A comprehensive immunological study was conducted in three calve groups vaccinated subcutaneously with three formulae of polyvalent FMD where group (A) was vaccine formula with AgNPs adjuvant, group (B) the vaccine formula adjuvanted with both MontanidISA 206 oil and AgNPs, while group (C) the vaccine formula with MontanidISA 206 oil adjuvant. A forth calve group kept without vaccination as control.